2021
DOI: 10.1093/mnras/stab540
|View full text |Cite
|
Sign up to set email alerts
|

GAMA/DEVILS: constraining the cosmic star formation history from improved measurements of the 0.3–2.2  μm extragalactic background light

Abstract: We present a revised measurement of the optical extragalactic background light (EBL), based on the contribution of resolved galaxies to the integrated galaxy light (IGL). The cosmic optical background radiation (COB), encodes the light generated by star-formation, and provides a wealth of information about the cosmic star formation history (CSFH). We combine wide and deep galaxy number counts from the Galaxy And Mass Assembly survey (GAMA) and Deep Extragalactic VIsible Legacy Survey (DEVILS), along with the H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 92 publications
7
61
0
Order By: Relevance
“…The SFR density at lookback times larger than 1 Gyr, shown as a black solid line, follows the Fermi-LAT constraints parametrized by Ref. [16] (see Table 5, initial SFR normalization). The local overdensity at shorter lookback times in the Northern and Southern hermispheres as well as in the Zone of Avoidance are estimated from our catalog and illustrated by colored lines, as labeled in the figure.…”
Section: A Cosmographic View On Stellar Mass and Star Formationsupporting
confidence: 57%
See 1 more Smart Citation
“…The SFR density at lookback times larger than 1 Gyr, shown as a black solid line, follows the Fermi-LAT constraints parametrized by Ref. [16] (see Table 5, initial SFR normalization). The local overdensity at shorter lookback times in the Northern and Southern hermispheres as well as in the Zone of Avoidance are estimated from our catalog and illustrated by colored lines, as labeled in the figure.…”
Section: A Cosmographic View On Stellar Mass and Star Formationsupporting
confidence: 57%
“…Figure 1:The star formation history from cosmic dawn down to the past billion year. The SFR density at lookback times larger than 1 Gyr, shown as a black solid line, follows the Fermi-LAT constraints parametrized by Ref [16]. (see Table5, initial SFR normalization).…”
supporting
confidence: 60%
“…While the merits and failings of these approaches can be argued -through numerous tests we have found that the P F approach is far less likely to go catastrophically wrong and produces more robust photometric measurements. For full details on P F and numerous tests, we refer the reader to the code description paper and four recent applications to the DEVILS input catalogue (Davies et al 2018), GAMA photometry (Bellstedt et al 2020), the VISTA VIKING datasets (Koushan et al 2021) and evolution of the high redshift stellar mass function (Adams et al 2020).…”
Section: The Need For a New Cosmos (D10) Photometric Cataloguementioning
confidence: 99%
“…catalogues to produce deep galaxy number counts as an additional photometric validation, for the purposes of exploring the overall galaxy population in broader studies, and for tuning numerical simulations of the galaxy distribution. These number counts have recently been used in Koushan et al (2021) to measure the Extragalactic Background Light (EBL) from the UV-MIR. Hence, we do not go into detail regarding the scientific implications of these distributions, but simply produce them and make available to the wider community.…”
Section: Deep Number Countsmentioning
confidence: 99%
See 1 more Smart Citation